Case Report: Cognitive Conversion in a Non-brazilian VAPB Mutation Carrier (ALS8) - Temp, Anna G. M.; Dyrba, Martin; Kasper, Elisabeth; Teipel, Stefan; Prudlo, Johannes (Frontiers in Neurology, 2021)
Amyotrophic lateral sclerosis 8 (ALS8) is a predominantly lower motor neuron syndrome originally described in a Portuguese-Brazilian family, which originated from a common founder. ALS8 is caused by a VAPB mutation and extremely rare in Central Europe. We present a 51-year-old German man with ALS8 whose P56S VAPB mutation was independent of the founder effect. In the final four years of his life (disease duration 10 years), the patient had five MRI scans and four in-depth neuropsychological assessments. This paper addresses the course of the patient’s cognitive status and relates cognitive performance to structural brain changes in order to determine whether this ALS8 case showed a different pattern of cognitive decline when compared with sporadic ALS. The executive functions, verbal fluency, and memory of the patient and 17 age, sex and education-matched controls were assessed on four different occasions. His cognitive performance and decline were investigated for abnormality using cross-sectional and longitudinal matched case-control analysis. We obtained five T1-weighted MRI, which we analysed using a voxel-wise non-parametric analysis with Statistical non-Parametric Mapping in Matlab. We also conducted a single subject correlation between cognitive performance and brain atrophy. The cognitive profile of the index patient featured executive dysfunctioning. Notably, his working memory and shifting ability declined from a healthy baseline to an impaired performance, leading to a transition from cognitively non-impaired (ALSni) to cognitively impaired (ALSci). The correlations we observed between cerebellar atrophy and verbal fluency in addition to fusiform gyrus atrophy and shifting are novel findings. We show that the conversion from ALSni to ALSci was associated with widespread cerebral atrophy, which extended beyond the primary motor and premotor cortex and affected, among others, the cerebellum and left fusiform gyrus. The index patients’ cognitive profile resembled that of sporadic ALS but the extensive atrophy beyond extra-motor areas has not yet been described.